A Comparative Analysis of Effectiveness of Learner-centered Approach and Teacher-centered Approach in Writing Skills of undergraduate students - Dr. Arshad Khan; Maimoona Nazneen; Sumera Shan Ahmad; Amina Khalid (Linguistics and Literature Review, 2016)
The research article investigates the effectiveness of Learner Centered Approach on the development of writing skills of undergraduate students. It is an experimental study on 60 undergraduate students of first semester in University of Management and Technology, Lahore. The participants were divided into two groups of 30. One group was taught through the Learner Centered Approach and the other was taught through Teacher Centered Approach. A pre-test was conducted at the start of the experiment to assess the performance of students at initial stage. The Teacher Centered Class was taught writing skills through Teacher Centered based activities and the Learner Centered Class was taught writing skills through Learner Centered activities. At the end of the experiment, a post test was conducted in order to assess the effect of the two approaches on the writing performance of the students. Ten (10) activities were conducted in total. IELTS assessment method was used to assess the performance of students in the pre-test, post-test and in the activities conducted during the experiment. The quantitative analysis was done through SPSS 21. The scores of the pre-test and post-test were compared to determine the approach that had relatively more positive effects on the writing skill of students. The results of the study show that the Learner Centered Approach is more effective in developing writing skills of undergraduate students at University of Management and Technology, Lahore.